1990
DOI: 10.1530/acta.0.1220417
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodine therapy in voluminous multinodular non-toxic goitre

Abstract: Large doses of radioiodione were administered since 1969 to 15 euthyroid patients with compressive voluminous goitres. A decrease in goitre size was observed in all patients (between 15 and 63%, average 39%). Maximal effect on goitre size was attained rapidly, partially already after less than one year and was almost maximal after 24 to 30 months. No significant local adverse reactions were observed; no patient required steroid administration. Hypothyroidism followed radioiodine administration in 30% of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 5 publications
3
30
0
3
Order By: Relevance
“…The authors of the studies with a longer follow-up report as much as a 71.9 % reduction [21]. Verelst et al observed the best results after less than a year of treatment with a nearly maximum effect 24 to 30 months after the therapy [23]. Similarly to what Nygaard et al reported in toxic goitre, we observed the greatest decrease in goitre volume within the first 3 months after the treatment, with a subsequent decrease in reduction degree [2].…”
Section: Discussionsupporting
confidence: 84%
“…The authors of the studies with a longer follow-up report as much as a 71.9 % reduction [21]. Verelst et al observed the best results after less than a year of treatment with a nearly maximum effect 24 to 30 months after the therapy [23]. Similarly to what Nygaard et al reported in toxic goitre, we observed the greatest decrease in goitre volume within the first 3 months after the treatment, with a subsequent decrease in reduction degree [2].…”
Section: Discussionsupporting
confidence: 84%
“…Huysmans et al (78) reported that 67% of the patients improved or were cured of dyspnoea or stridor, and even more were relieved of dysphagia. In other studies (69,76,77), the vast majority of patients reported satisfaction with the outcome of therapy.…”
Section: Efficacy Of 131mentioning
confidence: 63%
“…Despite the fact that RIT has been used in the treatment of thyroid diseases for over 70 years, some authors still consider it to be an unreliable method producing no satisfying results in the case of non-toxic nodular goiter [5,6,19,20]. First reports on Original non-invasive attempts at reducing goiter volume with I-131 were published at the beginning of the 1990s [21,22].…”
Section: Discussionmentioning
confidence: 99%